Financial System Vulnerability Indicators in Indonesia - Suidarma, I. Made; Indrawati, Yulia; Nengah Darma Diatmika, I. Gusti; Anggaradana, I. Nyoman (International Journal of Economics and Financial Issues, 2017)
The objective of this research is to analyze the indicators that cause vulnerability to financial system stability in Indonesia. The data used in this research is secondary data monthly with a range of 2006.1 to 2015.6. The method were used in this study Markov Switching Vector Autoregressive (MSVAR). The indicators used in this analysis are development of financial indicators, the financial vulnerability indicators, and the world economic climate indicator. The results of this study showed that overall, the indicators used as an early detection of vulnerability to financial system stability in Indonesia is showing signs of permanent especially on some variables that are the growth of credit to total GDP, interest rate spread, the fiscal deficit, current account, exchange rates and interest rate differentials. Credit to deposit ratio indicator does not allow instability in the financial system in Indonesia compared to the ratio of credit to GDP indicator. Inflation indicator showed chances of a crisis were small and not significant permanent. Indicators of capital transactions showed a smaller probability of the crisis compared to the current account. Keywords: Early Warning Indicators, Financial Stability, Markov Switching JEL Classifications: G17, G10, C34